Femfit Sync: Workout Application with Menstrual Tracker - Sairee Jasmi, Che Nor Fatihah; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2025)
The integration of digital technology into health and fitness has revealed a key gap: the lack of synchronization between menstrual and workout tracking apps, causing fragmented insights and potential health risks. This research develops a mobile application that unifies menstrual tracking with workout planning to deliver personalized fitness experiences for women aged 18–45. Using an object-oriented approach and system prototype methodology, the Android-based app is designed and tested for functionality, usability, and adaptability across menstrual phases. It tailors exercise plans based on menstrual data, reducing fatigue and injury risks from misaligned routines. Initial testing within the UTHM community shows improved user satisfaction, better workout planning, and higher health awareness. The study concludes that integrating physiological data into fitness platforms provides a more holistic, user-centered experience. Future enhancements will explore real-time synchronization via wearable devices to further automate and enrich user interaction.